28th International Symposium on Atmospheric and Ocean Optics: Atmospheric Physics 2022
DOI: 10.1117/12.2644931
|View full text |Cite
|
Sign up to set email alerts
|

Results of ship-based lidar studies of atmospheric aerosol fields over the water area of Lake Baikal

Abstract: The paper presents the results of lidar observations of the atmosphere over the water area of Lake Baikal. Integrated shipboard research using the research vessel «Academician V.A. Koptyug», are held annually, using the LOSA-A2 lidar, as well as local means (gas analyzers). Additionally, satellite data and information about the meteorological parameters of the atmosphere during the experiments are involved. The route of the ship goes all over the lake. An analysis is being carried out to identify the main sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The ecosystems of Lake Baikal, which have been experiencing significant anthropogenic pressures for decades, have not become an exception. As previous studies have shown, the southern part of the lake, to the north-west of which industrial centers using powerful coal-fired thermal power plants as energy sources are located, is the most susceptible to the anthropogenic impact [4][5][6][7][8][9] . The main pollutants emitted during their activities are oxides of sulfur, nitrogen, carbon and suspended solids 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The ecosystems of Lake Baikal, which have been experiencing significant anthropogenic pressures for decades, have not become an exception. As previous studies have shown, the southern part of the lake, to the north-west of which industrial centers using powerful coal-fired thermal power plants as energy sources are located, is the most susceptible to the anthropogenic impact [4][5][6][7][8][9] . The main pollutants emitted during their activities are oxides of sulfur, nitrogen, carbon and suspended solids 10 .…”
Section: Introductionmentioning
confidence: 99%